The lactate to albumin ratio linked to all-cause mortality in critically ill patients with septic myocardial injury - Chen, Sheng; Guan, Senhong; Yan, Zhaohan; Ouyang, Fengshan; Li, Shuhuan; Liu, Lanyuan; Zhong, Jiankai (Frontiers in Cardiovascular Medicine, 2023)
Background The lactate to albumin ratio (LAR) has emerged as a promising prognostic marker in critically ill patients. Despite its potential utility, the prognostic value of LAR in septic myocardial injury (SMI) remains uncertain. Methods This study aims to investigate the prognostic significance of LAR in SMI through a retrospective cohort analysis of data from the Medical Information Mart for Intensive Care III (MIMIC-III) (v1.4) database. The study included intensive care unit (ICU)-admitted patients (age ≥18 years) diagnosed with SMI. The primary endpoint was in-hospital mortality. Results A total of 704 patients were included in the study, of which 59.10% were male. Hospital mortality and ICU mortality rates were recorded at 29.97% and 22.87%, respectively. After adjusting for confounding factors, multivariate Cox proportional risk analysis demonstrated that LAR was independently associated with an increased risk of both hospital mortality (HR, 1.39 [95% CI: 1.24–1.56] P < 0.001) and ICU mortality (HR, 1.46 [95% CI: 1.29–1.65] P < 0.001). Furthermore, the generalized additive model (GAM) and restricted cubic spline (RCS) model indicated a linear relationship between LAR and mortality rates in the ICU and hospital. Conclusions The LAR may serve as a potential prognostic biomarker in critically ill patients with SMI. High LAR levels are associated with a higher risk of in-hospital mortality and can help identify individuals with high mortality rates. Overall, the findings emphasize the importance of using LAR as a tool for risk stratification and management of critically ill patients with SMI.